2020
DOI: 10.1111/1753-0407.13098
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of coronavirus disease 2019 infections among diabetics: A retrospective and multicenter study in China

Abstract: Background: Coronavirus disease 2019 (COVID-19) emerged in December 2019 and has spread globally. Diabetics are at increased risk of infections caused by a variety of pathogens including viruses. The present research aims to describe clinical characteristics and outcomes of COVID-19 patients with diabetes. Methods: A retrospective multicenter study of COVID-19 patients with diabetes was conducted in four hospitals in Wuhan, Shanghai, and Anhui Province. Reverse transcription polymerase chain reaction or next-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Table 1 presents the characteristics of the included studies. All eight studies were retrospective cohort studies, consisting of four from China, 4,[29][30][31] two from Italy 25,26 and two from the United States. 27,28 All studies were conducted during the first 5 months of the pandemic (i.e.…”
Section: (Statacorp College Station Tx Usa)mentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the characteristics of the included studies. All eight studies were retrospective cohort studies, consisting of four from China, 4,[29][30][31] two from Italy 25,26 and two from the United States. 27,28 All studies were conducted during the first 5 months of the pandemic (i.e.…”
Section: (Statacorp College Station Tx Usa)mentioning
confidence: 99%
“…A total of eight studies were included in the final analysis 4,[25][26][27][28][29][30][31] (see Figure S2 for the PRISMA flow diagram). Table 1 presents the characteristics of the included studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al [ 10 ] found that patients with diabetes needed more medical interventions and had more frequent multiple organ injury events than patients without diabetes. Huahua et al [ 11 ] found that patients with diabetes and COVID-19 developed more severe disease, had more complications (such as ARDS and AKI), required ICU admission more often, and had higher mortality than patients without diabetes. Sardu et al [ 12 ] also support similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the significant multifaceted effects of the pandemic, especially in chronic diseases, liver damage can be highly variable and complex, leading to the activation of an intra-hepatic immune response, triggering microvascular thrombosis, hepatic obstruction and systemic inflammation in addition to drug toxicity. In conjunction, this systemic disorder is often associated with a phenomenon known as “bystander hepatitis” and the patient can have a lethal course and show no specific signs of hepatic failure[ 101 , 102 ]. The personal care of these patients relies greatly on the regional COVID-19 prevalence and the laws and guidelines imposed[ 101 ].…”
Section: Recommendations For the Management Of Patients With Liver DImentioning
confidence: 99%